Product Market Regulation In Bulgaria : A Comparison With OECD Countries - Fay, Marianne (The World Bank, 2007)
Less restrictive product market policies are crucial in promoting convergence to higher levels of GDP per capita. This paper benchmarks product market policies in Bulgaria to those of OECD countries by estimating OECD indicators of Product Market Regulation (PMR). The PMR indicators allow a comprehensive mapping of policies affecting competition in product markets. Comparison with OECD countries reveals that Bulgaria has made substantial progress towards less restrictive product market policies but also emphasizes a number of areas where further reform is needed. These include adoption of a regulatory process based on incentive-based rather than command-and-control approach, reduction of state interference in the decision of state-owned enterprises, further streamlining of business licensing procedures, and improvement in the communication of rules and procedures to affected parties